NURSE'S MANAGERIAL COMPETENCE: KNOWLEDGE PUBLISHED IN BRAZILIANPERIODICALS - Juliana Helena Montezeli; Aida Maris Peres (Universidade Federal do Paraná, 2009)
Bibliographical research that aimed to analyze the publications in Brazilian periodicals from 2001 to 2007about the managerial competence of nurses. Using the descriptors nursing/organization/administration to search inLILACS and SciELO, 36 articles were found, 20 of which suited the inclusion criteria. From the grouping of the textsaccording to the focus given to management, 2 categories emerged: the dichotomy between the nurses' management andcare activities and the nurses' managerial competence and academic training. It was verified that it is essential that themanagement conducted by nurses focus on the care, thus, for this to happen, a change is necessary in management andcare, consistency between the academy, the world of the work and professional attitude. It was concluded that theanachronistic view of some nurses, health and higher education institutions is an obstacle that needs to be overcome forthe mobilization of managerial skills looking for a quality nursing care.